Uji Validitas LKS IPA Berbasis CTL Untuk Meningkatkan Kemampuan Berpikir Kritis Siiswa - Alfiana, Wakhidatul Alfana; Wulandari, Tabitha Sri Hartati (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2022)
This study aims to determine the design and validity of the science worksheets based on contextual teaching and learning on environmental pollution materials to improve students' critical thinking skills. This research is a development research using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The worksheets that have been developed then go through a validation stage by material experts and media experts who are lecturers at PGRI Ronggolawe University Tuban. After going through the revision stage, the science worksheets based on contextual teaching and learning were then tested on users, namely science teachers and seventh grade junior high school students. The science worksheets based on contextual teaching and learning obtained good results from experts, namely 89.7% from media experts and 94,2% from material experts. Based on these results, this IPA LKS is declared to be very valid and worthy of being tested by users, although with a few suggestions and improvements. After going through the expert validation stage, the science worksheets were then tested on users and showed good results, namely 94.1% of science teachers and 90,5% of seventh grade junior high school students. From the results of the assessment of the users of LKS IPA based on contextual teaching and learning, the results are very valid. The conclusion of this study states that the science worksheets based on contextual teaching and learning on environmental pollution materials to improve students' critical thinking skills are stated to be very valid and feasible to be used as student learning materials.